2019
DOI: 10.1186/s12862-019-1454-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple independent L-gulonolactone oxidase (GULO) gene losses and vitamin C synthesis reacquisition events in non-Deuterostomian animal species

Abstract: Background L-ascorbate (Vitamin C) is an important antioxidant and co-factor in eukaryotic cells, and in mammals it is indispensable for brain development and cognitive function. Vertebrates usually become L-ascorbate auxothrophs when the last enzyme of the synthetic pathway, an L-gulonolactone oxidase ( GULO ), is lost. Since Protostomes were until recently thought not to have a GULO gene, they were considered to be auxothrophs for Vitamin C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…24,25 Vitamin C, also known as ascorbic acid, is also an essential water-soluble vitamin in humans. Vitamin C cannot be synthesized in humans due to the loss of a functional L-gulonolactone oxidase (GULO) gene, 26 so we must obtain vitamin C from food. In addition to participating in the regulation of the immune system, vitamin C participates in various metabolic processes as a coenzyme, is involved in tissue repair, and has anti-oxidant properties, 27 besides, vitamin C may also exhibit a prooxidative effect antitumor at high doses.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Vitamin C, also known as ascorbic acid, is also an essential water-soluble vitamin in humans. Vitamin C cannot be synthesized in humans due to the loss of a functional L-gulonolactone oxidase (GULO) gene, 26 so we must obtain vitamin C from food. In addition to participating in the regulation of the immune system, vitamin C participates in various metabolic processes as a coenzyme, is involved in tissue repair, and has anti-oxidant properties, 27 besides, vitamin C may also exhibit a prooxidative effect antitumor at high doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, humans do not express l-gluconolactone oxidase, an important enzyme in the biosynthetic pathway of VC. Therefore, humans cannot biosynthesize VC, even though VC is an essential nutrient for humans (8,9). VC has a characteristic chemical structure of an enediol group (HO-C5C-OH), which is a free radical such as a superoxide anion radical (O2 2 ) and hydroxyl radical (-OH), and the function of an electron donor to supply electrons to radicals (9).…”
mentioning
confidence: 99%
“…Therefore, humans cannot biosynthesize VC, even though VC is an essential nutrient for humans (8,9). VC has a characteristic chemical structure of an enediol group (HO-C5C-OH), which is a free radical such as a superoxide anion radical (O2 2 ) and hydroxyl radical (-OH), and the function of an electron donor to supply electrons to radicals (9). By this action, VC has a strong antioxidant activity such as protecting important biomolecules, including proteins, lipids, and nucleic acids, from damage by oxidants.…”
mentioning
confidence: 99%
“…Studies on fruit‐eating Rousettus leschenaultii , insectivorous Hipposideros armiger (Cui et al, 2011a; 2011b) and Passeriformes birds (Drouin et al, 2011) have confirmed that the VC synthesis ability of animals may not be associated with their food habits and may instead be associated with evolutionary neutral selection pressure. The results of molecular evolution analysis of 11 animals with Gulo gene deletion also support this view (Henriques et al, 2019). Therefore, some insects may also have the ability to synthesize VC, a pathway that has the potential for genetic evolutionary selection.…”
Section: Introductionmentioning
confidence: 69%